Investigation on Turbulent Nanofluid Flow in Helical Tube in Tube Heat Exchangers - Puriya Mohamad Gholy Nejad; Ali Reza Solaimany Nazar; Zohreh Rahimi Ahar; Hajar Rajati (Journal of Heat and Mass Transfer Research, 2019)
In this study, the thermal characteristics of turbulent nanofluid flow in a helical tube in the tube heat exchanger (HTTHE) were assessed numerically through computational fluid dynamics (CFD) simulation. The findings of both the turbulent models: realizable k-epsion (k-ε) and re-normalisation group (RNG) k-epsilon were compared. The temperature distribution contours show that realizable and RNG k-ε models, together with the swirl dominated flow are of more uniform temperature distributions. The proper prediction of two layer theory leads to having a uniform temperature distribution and proper dimensionless wall distance (Y+). The turbulent flow and heat transfer of two nanofluids (SiO2, Al2O3) and base fluid with respect to swirl dominated flow was simulated through the RNG model. The effects of the concentration of nanoparticles on heat transfer characteristics in HTTHE and two turbulent models were analyzed in a comprehensive manner. It is concluded that up to 1% concentration of SiO2 and 1% concentration of Al2O3, similar heat transfer characteristics are observed. Comparison between the CFD results with the predicted values for friction factor coefficient (f) and Nusselt number (Nu) calculated through experimental correlations indicate the maximum errors of 6.56% and 0.27%, respectively.